(3GdOQQ GddhGeY HJMQjQ LeY GdLhGeYs - (3dGHf CHi GdTQjas; (3JGL GdOjf GdSHcj , CHh fUQ,J (B771 (3g` s
(3ChdgG (B:s
(3hCbhd Cfg deG cGf cJGH LeY GdLhGeY JCdja GdYdGeI bGVi GdbVGI JGL GdOjf CHj fUQ YHO GdhgGH Hf TjN GdESdGe bGVi GdbVGI Jbi GdOjf CHj GdMSf GdSHci MOGfi Pdc Edi JYdjb GdMhGTi s
(3BNQgG (B:s
(3bhdg dYOe EfVHGWgG aEf eQGJH GdKbg dG JMUi s
(3GdfSNI HgG MhGTs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B184 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B225s
(3JHUQGJ GdCUd (B:s
Keywords: (3Gdabg GdTGaYjs